Genetic risk assessment for hereditary renal cell carcinoma: Clinical consensus statement. Issue 21 (3rd August 2021) - Bratslavsky, Gennady; Mendhiratta, Neil; Daneshvar, Michael; Brugarolas, James; Ball, Mark W.; Metwalli, Adam; Nathanson, Katherine L.; Pierorazio, Phillip M.; Boris, Ronald S.; Singer, Eric A.; Carlo, Maria I.; Daly, Mary B.; et al.
Abstract : Background: Although renal cell carcinoma (RCC) is believed to have a strong hereditary component, there is a paucity of published guidelines for genetic risk assessment. A panel of experts was convened to gauge current opinions. Methods: A North American multidisciplinary panel with expertise in hereditary RCC, including urologists, medical oncologists, clinical geneticists, genetic counselors, and patient advocates, was convened. Before the summit, a modified Delphi methodology was used to generate, review, and curate a set of consensus questions regarding RCC genetic risk assessment. Uniform consensus was defined as ≥85% agreement on particular questions. Results: Thirty‐three panelists, including urologists (n = 13), medical oncologists (n = 12), genetic counselors and clinical geneticists (n = 6), and patient advocates (n = 2), reviewed 53 curated consensus questions. Uniform consensus was achieved on 30 statements in specific areas that addressed for whom, what, when, and how genetic testing should be performed. Topics of consensus included the family history criteria, which should trigger further assessment, the need for risk assessment in those with bilateral or multifocal disease and/or specific histology, the utility of multigene panel testing, and acceptance of clinician‐based counseling and testing by those who have experience with hereditary RCC. Conclusions: In the first ever consensus panel on RCC genetic risk assessment, 30 consensus statements were reached. Areas that require further research and discussion were also identified, with a second future meeting planned. This consensus statement may provide further guidance for clinicians when considering RCC genetic risk assessment. Lay Summary: The contribution of germline genetics to the development of renal cell carcinoma (RCC) has long been recognized. However, there is a paucity of guidelines to define how and when genetic risk assessment should be performed for patients with known or suspected hereditary RCC. Without guidelines, clinicians struggle to define who requires further evaluation, when risk assessment or testing should be done, which genes should be considered, and how counseling and/or testing should be performed. To this end, a multidisciplinary panel of national experts was convened to gauge current opinion on genetic risk assessment in RCC and to enumerate a set of recommendations to guide clinicians when evaluating individuals with suspected hereditary kidney cancer. Abstract : These consensus statements from an expert panel address a critical gap in published guidelines for genetic risk assessment in hereditary renal cell carcinoma. The findings of this panel reflect current opinion on who, what, when, and how genetic evaluation should be performed and may serve as an initial guideline for providers treating patients with suspected hereditary renal cell carcinoma.